Senam Aerobik Low Impact dapat Menurunkan Tekanan Darah pada Lansia dengan Hipertensi: Low Impact Aerobics Gymnastics Can Lower Blood Pressure in the Elderly with Hypertension - Nurafifah , Adethia Siti (Indonesian Scholar Journal of Nursing and Midwifery Science, 2021)
Introduction: Hypertension is the number 3 cause of death after stroke and tuberculosis which reaches 6,7% and the population of death at all ages in indonesia, non pharmacological treatment is proven to be able to control blood pressureso that pharmocological treatment is no longer needed or at least delayed,one of the non- pharmacological treatment that can be done by elderly hypertensi is hypertension is physical activity or mild exercise. The objective in this study is to know the aerobic gymnastics low impact on blood pressure by hypertension in elderly. Method: The kind of research is a quasi experimental with one group pre and post test design with control. The sample collection purposive use sampling techniques, with the rest of 16 respondents. The research uses a measuring instrument sphygmomanometer. Result: statistical tests using the t dependent, the significance of systolic blood pressure pre test-sistolik post = 0,01 test the p. Blood pressure diastolik pre test-diastolik post test. Discussion: From the results of research that has been carried out, it is found that respondents who intervened by doing low impact aerobic exercise on the elderly, namely there was an effect of giving low impact aerobic exercise on the elderly who had hypertension. In conclusion there is influence gymnastic aerobic low the blood pressure or hypertension in elderly.